(untitled) (Neo Scientific Peer Reviewed Journal, 2026)
This article provides a comprehensive overview of hepatitis, including its types, transmission methods, clinical manifestations, diagnostic approaches, treatment options, and preventive measures. It aims to enhance understanding of the disease and its impact on public health.